2016
DOI: 10.18632/oncotarget.10602
|View full text |Cite
|
Sign up to set email alerts
|

[64Cu]XYIMSR-06: A dual-motif CAIX ligand for PET imaging of clear cell renal cell carcinoma

Abstract: Carbonic anhydrase IX (CAIX) is a cell surface enzyme that is over-expressed in approximately 95% of cases of clear cell renal cell carcinoma (ccRCC), the most common renal cancer. We synthesized and performed in vitro and in vivo evaluation of a dual-motif ligand, [64Cu]XYIMSR-06, for imaging CAIX expression on ccRCC tumors using positron emission tomography (PET). [64Cu]XYIMSR-06 was generated in yields of 51.0 ± 4.5% (n=5) and specific activities of 4.1 – 8.9 GBq/μmol (110-240 Ci/mmol). Tumor was visualized… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
53
0

Year Published

2017
2017
2024
2024

Publication Types

Select...
7
2

Relationship

1
8

Authors

Journals

citations
Cited by 53 publications
(53 citation statements)
references
References 41 publications
0
53
0
Order By: Relevance
“…Most recently, Pomper's group radiolabeled a dual motif CA-IX inhibitor consisting of a 4,4-bis(4-hydroxyphenyl)valeric acid and a succinyl acetazolamide group with 111 In (via DOTA chelator) and 64 Cu (via NOTA chelator) and acheived tumor uptakes values of 14.5-26.0%ID/g at 1 h p.i. 29,30 . Krall et al 31 reported the synthesis and evaluation of a 99m Tc-labeled acetazolamide derivative with excellent tumor targeting (22%ID/g at 3 h p.i.)…”
Section: Resultsmentioning
confidence: 99%
See 1 more Smart Citation
“…Most recently, Pomper's group radiolabeled a dual motif CA-IX inhibitor consisting of a 4,4-bis(4-hydroxyphenyl)valeric acid and a succinyl acetazolamide group with 111 In (via DOTA chelator) and 64 Cu (via NOTA chelator) and acheived tumor uptakes values of 14.5-26.0%ID/g at 1 h p.i. 29,30 . Krall et al 31 reported the synthesis and evaluation of a 99m Tc-labeled acetazolamide derivative with excellent tumor targeting (22%ID/g at 3 h p.i.)…”
Section: Resultsmentioning
confidence: 99%
“…CA-IX inhibitors have also been used as delivery vectors of cytotoxic payloads to target tumor cells within hypoxic niches [16][17][18] . Complementing these therapeutic efforts has been the development of CA-IX radiotracers derived from inhibitors for positron emission tomography (PET) and single photon emission computed tomography (SPECT) applications [19][20][21][22][23][24][25][26][27][28][29][30][31] . PET and SPECT can generate images of high resolution and sensitivity, while providing quantitative information on drug target expression.…”
Section: Introductionmentioning
confidence: 99%
“…Minn et al [ 45 ] developed a novel dual motif ligand for PET/CT detection of localized and metastatic ccRCC. 64 Cu-XYIMSR-06 is a small size synthesized molecule added with radioactive copper, presenting high affinity for CAIX.…”
Section: Evidence Synthesismentioning
confidence: 99%
“…Recent findings of deficient 13 C-lactate production in isocitrate dehydrogenase 1 mutant brain tumours, compared to glioblastomas, for example, provide also opportunities for tumour typing with hyperPET. Besides direct clinical application, the multiplexing of MR using hyperpolarized bicarbonate (H 13 CO3 -) with other techniques evaluating tissue acidity 183 and carbonic anhydrase-IX (CAIX) expression [184][185][186] could improve the understanding of the relationship between pH of tumour tissue and its microenvironment, and could potentially lead to the clinical translation of these agents.…”
Section: Imaging Physiology In Patientsmentioning
confidence: 99%